ЗАХИСТ ЕЛЕКТРОСПОЖИВАЧІВ ВІД ВИСОКОВОЛЬТНИХ ІМПУЛЬСНИХ ЗАВАД ВЕЛИКОЇ ЕНЕРГІЇ МІКРОСЕКУНДНОГО ДІАПАЗОНУ ТРИВАЛОСТЕЙ У ПОЛЕГШЕНОМУ РЕЖИМІ НАВАНТАЖЕННЯ - Павловський, В.О.; Герасименко, П.Ю.; Гурін, В.К.; Юрченко, О.М.; Мугенов, Д.Д. (Інститут електродинаміки НАН України, Київ, 2026)
The paper considers features of consumer protection against microsecond high-voltage surges from the power grid under consumer’s partial load operation. A typical protection circuit containing a cascade-connected voltage limiter and a two-stage LC low-pass filter (LPF) is analyzed. Theoretical calculations and simulation studies of the response of the L-shaped LPF to an input voltage surge under the partial load operation of the electrical consumer were carried out, which showed an increase in the response amplitude. To reduce the response of the LPF, it is proposed to introduce resistors in series with each capacitor of the LPF. The results of simulation and experimental verification confirmed the effectiveness of the proposed addition – the maximum voltage surge at the consumer’s AC input decreased by up to 2 times. References 17, figures 12.